PERAN DOMAIN KOGNITIF, AFEKTIF, PSIKOMOTOR DALAM PEMBENTUKAN KOMPETENSI SISWA SMK: TINJAUAN SISTEMATIS - Hatta, Mega Amelia Prihatini; Savitri, Wici Aan; Koto, Rahmat Desman; Simatupang, Wakhinuddin; Yuliana, Yuliana; Wagino, Wagino (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Vocational education in Indonesia faces challenges in ensuring vocational school graduates have a combination of relevant technical and non-technical skills to meet the needs of a dynamic industry. This study aims to evaluate the role of cognitive, affective, and psychomotor domains in shaping the competencies of Vocational High School (SMK) students in Indonesia, especially in the context of vocational education. Using the Systematic Literature Review (SLR) approach, this study identifies and analyzes the findings of various studies related to developing the three domains. The results of the study show that mastery of these three domains is essential to equip students with the technical skills, professional attitudes, and mental readiness needed in the world of work. The cognitive domain contributes to developing analytical and problem-solving skills; the affective domain increases motivation and positive attitudes. In contrast, the psychomotor domain focuses on motor skills and practical skills. The study also recommends developing a balanced curriculum involving teacher training, multidimensional evaluation, and collaboration with industry to ensure that vocational school graduates are ready to face industry demands with relevant competencies.Keywords: cognitive, affective, psychomotor, student competence, vocational school.